ANALISIS SWOT PADA USAHA MIKRO KECIL MENENGAH (UMKM) NASI BEBEK RUMAHAN BERBASIS ONLINE DI ERA DIGITAL (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study employs the SWOT analysis framework (Strengths, Weaknesses, Opportunities, and Threats) to analyze internal and external factors affecting the online-based home-style duck rice MSME. The objective is to identify internal strengths and weaknesses as well as external opportunities and threats in order to formulate appropriate strategies to enhance competitiveness in the digital era. The methods used include observation, direct interviews, and literature studies. The results show that the main strengths of this business are the distinctive flavor of Madurese-style duck, affordable pricing, and a flexible online ordering system. However, weaknesses include limited production capacity, dependence on digital platforms, and a lack of branding. The greatest opportunities arise from the increasing consumption of ready-to-eat food through apps and the growing trend of local cuisine, while threats include intense competition and changes in delivery app algorithms. Recommended strategies include strengthening digital branding, product diversification, and technology-based operational optimization.